Bioprospecting Microbiome for Soil and Plant Health Management Amidst Huanglongbing Threat in Citrus: A Review - Srivastava, Anoop Kumar; Das, Ashis Kumar; Jagannadham, Prasanth Tej Kumar; Bora, Popy; Ansari, Firoz Ahmad; Bhate, Ruchi (Frontiers in Plant Science, 2022)
Microorganisms have dynamic and complex interactions with their hosts. Diverse microbial communities residing near, on, and within the plants called phytobiome, are an essential part of plant health and productivity. Exploiting citrus-associated microbiomes represents a scientific approach towards sustained and environment friendly module of citrus production, though periodically exposed to several threats, with Huanglongbing (HLB) predominantly being most influential. Exploring the composition and function of citrus microbiome, and possible microbial redesigning under HLB disease pressure, has sparked renewed interest in recent times. A concised account of various achievements in understanding the citrus associated microbiome, in various niche environments viz., rhizosphere, phyllosphere, endosphere, and core microbiota alongside their functional attributes has been thoroughly reviewed and presented. Efforts were also made to analyze the actual role of citrus microbiome in soil fertility and resilience, interaction with and suppression of invading pathogens along with native microbial-communities and their consequences thereupon. Despite the desired potential of the citrus microbiota to counter different pathogenic diseases, utilizing the citrus microbiome for beneficial applications at the field level is yet to be translated as a commercial product. We anticipate that advancement in multiomics technologies, high-throughput sequencing (HTS) and culturing, genome editing tools, artificial intelligence, and microbial consortia will provide some exciting avenues for citrus microbiome research and microbial manipulation to improve the health and productivity of citrus plants.